Digital Therapeutics: Exploring the Possibilities of Digital Intervention for Myopia - Lee, Yong Sun; Choi, Seung Eun; Hahm, Jarang; Kim, Myoung Joon; Bae, Hyo Sook; Yi, Kayoung; Lim, Hyun Taek; Hyon, Joon Young (Frontiers in Digital Health, 2021)
Pediatric myopia is increasing globally and has become a major public health issue. However, the mechanism of pediatric myopia is still poorly understood, and there is no effective treatment to prevent its progression. Based on results from animal and clinical studies, certain neuronal–humoral factors (NHFs), such as IGF-1, dopamine, and cortisol may be involved in the progression of pediatric myopia. Digital therapeutics uses evidence-based software as therapeutic interventions and it has the potential to offer innovative treatment strategies for pediatric myopia beyond conventional treatment methods. In this perspective article, we introduce digital therapeutics SAT-001, a software algorithm that modulates the level of NHFs to reduce the progression of pediatric myopia. The proposed mechanism is based on a theoretical hypothesis derived from scientific research and clinical studies and will be further confirmed by evidence generated from clinical studies involving pediatric myopia.